Cross Stitch Cards & Keepsakes - Verso, Jo (New York A David & Charles Craft Book, 1990)
Describes how to make greetings cards with personalized designs worked in cross stitch. There are cards for various occasions, with a range of small gifts such as a Valentine heart, a ring pillow, a pair of "Twelve Days of Christmas" wall hangings, and an Advent calendar.
Include Color Illustration and Index
Keywords: Cross-stitch -- Greeting cards